1998
DOI: 10.1136/jamia.1998.0050305
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Adverse Drug Events: Development of a Computer-based Monitor and Comparison with Chart Review and Stimulated Voluntary Report

Abstract: The computer-based monitor identified fewer ADEs than did chart review but many more ADEs than did stimulated voluntary report. The overlap among the ADEs identified using different methods was small, suggesting that the incidence of ADEs may be higher than previously reported and that different detection methods capture different events. The computer-based monitoring system represents an efficient approach for measuring ADE frequency and gauging the effectiveness of ADE prevention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
344
0
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(363 citation statements)
references
References 22 publications
13
344
0
6
Order By: Relevance
“…They also argue that the use of overall AEs as a measure of safety seems to overestimate the number of safety events that are preventable versus those that are inherent (as in the IOM reports). 1,48,49 pAEs are also the easiest errors for those who are unfamiliar with patient safety terminology to identify as areas for improvement. Those against the use of preventability measures cite that its assessment is unreliable 50 -52 , the definition of preventable changes as technology and research evolve, most AEs are preventable 53 , and determinations of preventability fail to take into account the existing disease and surrounding circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…They also argue that the use of overall AEs as a measure of safety seems to overestimate the number of safety events that are preventable versus those that are inherent (as in the IOM reports). 1,48,49 pAEs are also the easiest errors for those who are unfamiliar with patient safety terminology to identify as areas for improvement. Those against the use of preventability measures cite that its assessment is unreliable 50 -52 , the definition of preventable changes as technology and research evolve, most AEs are preventable 53 , and determinations of preventability fail to take into account the existing disease and surrounding circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…20 It is well known that voluntary and mandatory reporting systems for adverse events and ADE, including the FDA MDR database, suffer from severe underreporting; epidemiological studies revealed reporting rates that ranged from a low of 1.2% to a high of 7.7%. 2, [21][22][23] We used these extreme values to transform the minimum and maximum reported frequencies in Table I into evidence-based high and low estimates of the true incidence of patient mortality associated with programming errors with this device. The results are shown in Table II.…”
Section: éLéments Cliniquesmentioning
confidence: 99%
“…These actions may result in substantial changes in the organizational culture and practices that may lead to greater patient safety. Examples include computerized systems capable of detecting prescription errors and potential and actual ADEs [37][38][39]. These systems utilize rules to scan medication orders, laboratory results, etc.…”
Section: Simulation Modelmentioning
confidence: 99%